Propuesta de aplicación del e -commerce a la empresa de medicamentos FARMACOMERCIAL (2021)
The academic research entitled: Proposal for the application of e-commerce to the Pharmacometrician drug company, is a descriptive qualitative study whose general objective was to analyze how the level of sales and marketing of medicinal products of the company can be enhanced Farmacomercial SAS using E-commerce tools; For which they established as specific objectives to identify the strategies and the most pertinent technological tools to favor the levels of visibility and sales of products, this work was articulated the development of a strategic plan directed by a professional in digital marketing, which made it possible to establish strategies of Achievement and loyalty of new customers using digital platforms and social networks with the greatest presence and circulation in the country.